Dampak Bantuan Langsung Tunai (BLT) Bagi Masyarakat Akibat Covid-19 Di Desa Malaka Kecamatan Pemenang Kabupaten Lombok Utara - Fadila Aulia (Prodi Tadris Matematika-UIN Mataram, 2021)
Abstract The end of 2019 to be precise at the beginning of 2020. The Covid-19 pandemic has become a problem all over the world. The entire government is overwhelmed but continues to try to overcome the spread of the Covid-19 virus while at the same time overcoming the various impacts of one of the impacts caused by the Covid-19 pandemic. This is an economic factor. In Indonesia, due to the pandemic, the community’s economy has declined. And to overcome this, the government has made one of the efforts to reduce the burden on the community, namely refocusing the budget from various existing budget posts. And one of the the budget posts that was refocused was the Village Fund, the Village Fund which was actually intended for village development and development but was transferred to a cash transfer fund called Direct Cash Assistance (BLT). In the implementation of this program, in terms of the impact of the Direct Cash Assistance (BLT) program, many question are asked. This research was conducted in Malaka Village, Pemenang District, Nort Lombok Regency. The research finding show that the impact of this program, especially for the poor, is very beneficial for them, and some people very supportive of the program carried out by the central government. Keywords : BLT; Village Fund; Assistance